Essential oils of leaves and rhizomes of Kaempferia galanga Linn. - Bhuiyan, Md Nazrul Islam; Begum, Jaripa; Anwar, MN (Chittagong University Journal of Biological Sciences, 2013)
Kaempferia galanga Linn. leaf and rhizome oils, obtained by hydrodistillation, were analyzed by gas chromatography mass spectroscopy (GC-MS). One hundred and eight components were identified in the leaf oil. The major components were linoleoyl chloride (21.42%), caryophyllene oxide (11.75%), cubenol (9.66%) and caryophyllene (5.60%). Eighty one components were identified in rhizome oil with the main components being 2-propenoic acid, 3-(4-methoxyphenyl),-ethyl ester (63.36%), ethyl cinnamate (6.31%), 4-cyclooctene -1-methanol (4.61%), caryophyllene oxide (4.37%) and limonene (3.22%). The compositions of both oils varied qualitatively and quantitatively. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13407 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):65-76, 2008